Administrative leaders as institutional entrepreneurs in developing countries: A study of the development and institutionalization of performance management in Ghana's public service. (13th September 2019) - Ohemeng, Frank L.K.; Kamga, Osee
Summary: Performance management (PM) has become one of the most important reforms in the public sector in both developed and developing countries. Unfortunately, institutionalizing PM in the sector continues to be a major problem. Although a number of scholars continue to study the PM in the public sector from different theoretical perspectives, there has been paucity of research concerning the process of institutionalization. The few studies that have attempted to look at the process have done so from a "coercive isomorphism" perspective, especially through legislation. The lack of studies to examine the process of institutionalization has therefore created a gap, which needs to be filled. We therefore attempt to contribute to this discussion by exploring the role of institutional entrepreneurs and their impact on the development and institutionalization of PM in developing countries, with a particular focus on Ghana, a country obsessed with PM but was only able to institutionalize one in 2013 under the leadership of its Public Services Commission. How was the leadership of the PSC able to succeed where previous leaders could not? What characteristics did they display, and what strategies did they use to get things done? The research is a qualitative one.